Cross-sectional and longitudinal associations between serum 25-hydroxyvitamin D and cognitive functioning. (22nd December 2015) - van Schoor, N. M.; Comijs, H. C.; Llewellyn, D. J.; Lips, P.
ABSTRACT: Background: Vitamin D deficiency is common in older persons. The objectives of this study were: To examine the cross-sectional and longitudinal association between serum 25-hydroxyvitamin D (25(OH)D) and cognitive functioning in older persons; and to explore the optimal cut-off for serum 25(OH)D. Methods: Data of the Longitudinal Aging Study Amsterdam (LASA) were used. Serum 25(OH)D was determined using a competitive protein binding assay in 1995/6 ( n = 1, 320). Cognitive functioning was assessed in 1995/6 and 1998/9 using the Mini-Mental State Examination (MMSE, general cognitive functioning), Raven's Colored Progressive Matrices (RCPM, ability of nonverbal and abstract reasoning), the Coding Task (CT, information processing speed), and the 15 Words Test (15WT, immediate memory and delayed recall). The data were analyzed using linear regression analyses and restricted cubic spline functions. The MMSE was normalized using ln(31-MMSE). Results: Mean serum 25(OH)D was 53.7 nmol/L. After adjustment for confounding, patients with serum 25(OH)D levels below 30 nmol/L had significantly lower general cognitive functioning (beta of ln(31-MMSE) = 0.122; p = 0.046) and slower information processing speed (beta = −2.177, p = 0.001) as compared with patients having serum 25(OH)D levels ≥ 75 nmol/L in the cross-sectional analyses. For both outcomes, the optimal cut-off was about 60 nmol/L. No other significant associations were observed. Conclusions: A lower serum 25(OH)D was significantly associated with lower general cognitive functioning and slower information processing speed, but not with a faster rate of cognitive decline.